2016
DOI: 10.1016/j.chom.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Intestinal Bacteria Contain Putative Zwitterionic Capsular Polysaccharides with Anti-inflammatory Properties

Abstract: Summary Zwitterionic capsular polysaccharides (ZPS) are bacterial products that modulate T cells, including inducing anti-inflammatory IL-10-secreting T regulatory cells (Tregs). However, only a few diverse bacteria are known to modulate the host immune system via ZPS. We present a genomic screen for bacteria encoding ZPS molecules. We identify diverse host-associated bacteria, including commensals and pathogens with known anti-inflammatory properties, with the capacity to produce ZPSs. Human mononuclear cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 51 publications
7
100
0
1
Order By: Relevance
“…Intriguingly, a recent study showed that zwitterionic capsular polysaccharides derived from various commensal gut bacteria produce anti-inflammatory effects by inducing regulatory T cells 50. Our observations that P. goldsteinii treatment induces expression of IL-10 (figure 7H) and helps maintain intestinal integrity (figure 7G,I,J) support the possibility that the bacterium may preserve intestinal homeostasis and improve gut barrier functions in vivo.…”
Section: Discussionsupporting
confidence: 76%
“…Intriguingly, a recent study showed that zwitterionic capsular polysaccharides derived from various commensal gut bacteria produce anti-inflammatory effects by inducing regulatory T cells 50. Our observations that P. goldsteinii treatment induces expression of IL-10 (figure 7H) and helps maintain intestinal integrity (figure 7G,I,J) support the possibility that the bacterium may preserve intestinal homeostasis and improve gut barrier functions in vivo.…”
Section: Discussionsupporting
confidence: 76%
“…Fermentation of dietary fibers by Clostridia clusters IV, XIVa and XVIII produces short-chain fatty acids (SCFA), particularly butyrate, which exert significant anti-inflammatory functions, promote peripheral T reg cell generation, and are key nutrients for colonocytes 103106 . Moreover, subtypes of B. fragilis and certain other intestinal bacteria produce capsular polysaccharide A (PSA), which provides immunoprotection through induction of IL-10-producing T reg cells, and administration of B. fragilis or even PSA alone corrected immune defects in germ-free mice and had protective effects in models of colitis 107,108 . Further, the intestinal tissues of IBD patients often show downregulation of the aryl hydrocarbon receptor (AHR), which, in response to bacteria-derived indole metabolites, induces production of IL-22 by group 3 innate lymphoid cells (ILC3) 109 .…”
Section: The Hidden Microbial “Self” and Autoimmunitymentioning
confidence: 99%
“…2b). A recent study has identified additional gut commensals that produce zwitterionic capsular polysaccharides, including a strain of Bacteroides cellulosilyticus , with similar anti-inflammatory properties to PSA 114 .…”
Section: Bacteroides Modulation Of the Hostmentioning
confidence: 99%